Addressing Unmet Clinical Needs with 3D Printing Technologies. Issue 17 (13th July 2018) - Ghosh, Udayan; Ning, Shen; Wang, Yuzhu; Kong, Yong Lin
Abstract: Recent advances in 3D printing have enabled the creation of novel 3D constructs and devices with an unprecedented level of complexity, properties, and functionalities. In contrast to manufacturing techniques developed for mass production, 3D printing encompasses a broad class of fabrication technologies that can enable 1) the creation of highly customized and optimized 3D physical architectures from digital designs; 2) the synergistic integration of properties and functionalities of distinct classes of materials to create novel hybrid devices; and 3) a biocompatible fabrication approach that facilitates the creation and cointegration of biological constructs and systems. This progress report describes how these capabilities can potentially address a myriad of unmet clinical needs. First, the creation of 3D‐printed prosthetics to regain lost functionalities by providing structural support for skeletal and tubular organs is highlighted. Second, novel drug delivery strategies aided by 3D‐printed devices are described. Third, the advancement of medical research heralded by 3D‐printed tissue/organ‐on‐chips systems is discussed. Fourth, the developments of 3D‐printed tissue and organ regeneration are explored. Finally, the potential for seamless integration of engineered organs with active devices by leveraging the versatility of multimaterial 3D printing is envisioned. Abstract : Recent advances in 3D printing have enabled the creation of novel 3D constructs and devices with an unprecedented level of complexity, properties, and functionalities. This progress report describes how these capabilities can potentially address a myriad of unmet clinical needs and ultimately to provide better diagnostic tools and treatment strategies.